Chirp-Induced Channel of an Airy Pulse in an Optical Fiber Close to Its Zero-Dispersion Point - Fu Deng; Weiyi Hong (IEEE Photonics Journal)
We investigate the dynamics of a chirped Airy pulse in a fiber under the action of third-order dispersion. We found an interesting phenomenon in which the pulse is focused and where the pulse profile changes slowly within a distance of several dispersion lengths, which is named a channel. The amplitude and the length of the channel depends on the chirp parameter. The underlying physical mechanism for this phenomenon is also discussed.